\[\boxed{\text{321\ (321).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)* - \left( 3x^{2} - 4xy + 2y^{2} \right) =\]
\[= 9x^{2} + y^{2}\]
\[*\ =\]
\[= 9x^{2} + y^{2} + \left( 3x^{2} - 4xy + 2y^{2} \right)\]
\[*\ =\]
\[= 9x^{2} + y^{2} + 3x^{2} - 4xy + 2y^{2}\]
\[*\ = 12x^{2} - 4xy + 3y^{2}.\]
\[2)\ a^{3} - 6a^{2} + 2a - (*) =\]
\[= a^{5} + 2a^{2} - 7\]
\[*\ =\]
\[= a^{3} - 6a^{2} + 2a - \left( a^{5} + 2a^{2} - 7 \right)\]
\[*\ =\]
\[= a^{3} - 6a^{2} + 2a - a^{5} - 2a^{2} + 7\]
\[*\ = - a^{5} + a^{3} - 8a^{2} + 2a + 7\]
\[\boxed{\text{321.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ \left( 1\frac{1}{6} \right)^{9} \cdot \left( \frac{6}{7} \right)^{10} =\]
\[= \left( \frac{7}{6} \right)^{9} \cdot \left( \frac{6}{7} \right)^{10} = \frac{7^{9} \cdot 6^{10}}{6^{9} \cdot 7^{10}} = \frac{6}{7}\]
\[2)\ 5^{14} \cdot {0,2}^{12} = 5^{12} \cdot 5^{2} \cdot {0,2}^{12} =\]
\[= (5 \cdot 0,2)^{12} \cdot 5^{2} = 1 \cdot 5^{2} = 25\]
\[3)\ \left( - 1\frac{1}{3} \right)^{5} \cdot \left( \frac{3}{4} \right)^{8} =\]
\[= \left( - \frac{4}{3} \right)^{5} \cdot \left( \frac{3}{4} \right)^{8} = \frac{- 4^{5} \cdot 3^{8}}{3^{5} \cdot 4^{8}} =\]
\[= - \frac{3^{3}}{4^{3}} = - \frac{27}{64}\]